PENGARUH ANIL TERMAL TERHADAP BESARAN OPTIS LAPISAN TIPIS a-SiC:H HASIL METODE DC SPUTTERING II. TARGET GRAFIT - Saleh, Rosari; Munisa, Lusitra; Marianty, Dewi (UI Scholars Hub, 2003)
The Effect of Thermal Annealing on the Optical Properties of a-SiC:H Films Produced by DC Sputtering Methods: I. Graphite Target Case. A study of the annealing effect on optical properties and disorder of hydrogenated amorphous silicon carbon (a-SiC:H) films was undertaken. The films were prepared by sputtering technique using graphite target and silicon wafer in argon and hydrogen gas mixture, and then characterized by uv-vis (ultra violet-visible) spectroscopy before and after annealing. Index of refraction n and absorption coefficient α of films have been determined from measurements of transmittance. The optical gap show small variation with annealing temperature, increasing with increasing annealing temperature up to 500 °C. An increase of annealing temperature leads to reduced film density and the amorphous network disorder. The experimental results are discussed in terms of deposition condition and compared to other experimental results.